Influência do aerossol atmosférico no balanço de energia em uma região de transição na Amazônia Legal - Duarte, Leilane Gomes (2024)
The Earth's radiative balance can be disrupted by various factors, both environmental and anthropogenic. In this context, the Legal Amazon provides an ideal setting for further investigation, due to the presence of complex ecosystems and the significant amount of aerosols released into the atmosphere as a result of biomass burning in the region and surrounding areas.A study was conducted to examine the relationship between aerosol optical depth (AOD) and various surface fluxes. The results demonstrated significant effects of aerosol presence both on an hourly scale and over the entire period analyzed. Aerosol optical depth (AOD) is directly linked to the quantity of optically active particles present in the atmospheric column, making it a crucial variable in estimating the influence of aerosols on the energy balance. Consequently, this study carried out a comparative analysis of energy balances under different atmospheric conditions, distinguishing between clear skies, when AOD 0.071, and aerosol-laden days, when the optical depth AOD > 0.071. Energy balance estimates were performed using the Bowen Ratio Method, using in situ measurements of meteorological variables such as air temperature (T), relative humidity (RH), soil heat flux (G), and net radiation (Rn). Subsequently, using the hourly values of the balance components, a fourth-order polynomial fit was applied, allowing for estimates of energy flux densities and global radiation (Rg) under clear-sky conditions. Finally, the clearness index was calculated for both clear-sky conditions and aerosol-laden conditions. The hourly analysis of the data revealed that net radiation (Rn) and sensible heat flux (H) under aerosol conditions exhibited lower hourly values compared to those recorded under clear-sky conditions. The observed differences ranged from 3.89 to 15.64 for Rn and from 9.00 to 28.13 for H. Conversely, both latent heat flux (LE) and soil heat flux (G) showed significantly higher values when compared to estimates under clear-sky conditions. The observed differences ranged from 1.36 to 31.71 for LE and from 20.62 to 133.23 for G. When considering the entire period, under aerosol conditions, net radiation (Rn), latent heat flux (LE), sensible heat flux (H), and global radiation (Rg) were 18.51, 15.17, 44.10, and 3.83 lower, respectively, compared to the values recorded under clear-sky conditions. Meanwhile, soil heat flux (G) and the clearness index (kt) presented higher values, with percentage differences of 43.85 and 6.86, respectively.